VD_FINDINFO HC / 2010 / 275 vom 13. Januar 2010 - VD Tribunal cantonal (2010)
LIBÉRATION CONDITIONNELLE, MESURE THÉRAPEUTIQUE INSTITUTIONNELLE | 62 al. 1 CP, 62d al. 1 CP, 485m CPP, 26 al. 1 let. a LEP